2011
DOI: 10.1093/toxsci/kfr019
|View full text |Cite
|
Sign up to set email alerts
|

Differential Estrogenic Effects of the Persistent Organochlorine Pesticides Dieldrin, Endosulfan, and Lindane in Primary Neuronal Cultures

Abstract: The organochlorine chemicals endosulfan, dieldrin, and γ-hexachlorocyclohexane (lindane) are persistent pesticides to which people are exposed mainly via diet. Their antagonism of the γ-aminobutyric acid-A (GABA(A)) receptor makes them convulsants. They are also endocrine disruptors because of their interaction with the estrogen receptor (ER). Here, we study the effects of dieldrin, endosulfan, and lindane on ERs in primary cultures of cortical neurons (CN) and cerebellar granule cells (CGC). All the compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 52 publications
2
62
0
Order By: Relevance
“…Here, the former two showed similar strong antiestrogenicity with an EC 50 of 4.71 Â 10 À 7 and 4.03 Â 10 À 7 mol/L, respectively, which is consistent with the report that they had similar treatment efficacies in breast cancer (Howell et al, 2004). HCH performed as a weak ER antagonist in the recombinant yeast (EC 50 ¼4.60 Â 10 À 5 mol/L), although both its estrogenic and antiestrogenic activities have been observed in other organisms (Briz et al, 2011;Chadwick et al, 1988;Huang et al, 2006;Raizada et al, 1980). Because the binding of an antiestrogen to ER cannot initiate the expression of the reporter gene lac-Z, the inhibition effect test had to be executed by simultaneously exposing the yeast cells to E2 and the tested antagonist.…”
Section: Discussionsupporting
confidence: 89%
“…Here, the former two showed similar strong antiestrogenicity with an EC 50 of 4.71 Â 10 À 7 and 4.03 Â 10 À 7 mol/L, respectively, which is consistent with the report that they had similar treatment efficacies in breast cancer (Howell et al, 2004). HCH performed as a weak ER antagonist in the recombinant yeast (EC 50 ¼4.60 Â 10 À 5 mol/L), although both its estrogenic and antiestrogenic activities have been observed in other organisms (Briz et al, 2011;Chadwick et al, 1988;Huang et al, 2006;Raizada et al, 1980). Because the binding of an antiestrogen to ER cannot initiate the expression of the reporter gene lac-Z, the inhibition effect test had to be executed by simultaneously exposing the yeast cells to E2 and the tested antagonist.…”
Section: Discussionsupporting
confidence: 89%
“…Endosulfan has been reported to affect a variety of organ systems and physiologic functions (Moon and Chun, 2009). Animal studies have shown its toxicity to the liver, kidney, blood, immune, reproductive, and nervous systems (Choudhary and Joshi, 2003;Singh et al, 2008;Briz et al, 2011). Methoxychlor induces follicular atresia, reduces ovulation rate, and decreases embryo implantation in rats and mice (Tiemann, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine pesticides such as DDTs and its metabolites have a detrimental effect on the endocrine and reproductive systems in both wildlife and humans due to their ability to interact with hormone receptors especially estrogen receptor (Frigo et al, 2002;Guillette et al 1994;Jian Li et al 2008;Scippo et al 2004;Uchida et al 2010). HCB was found to stimulate estrogendependent cell proliferation in MCF-7 cells (Garcia et al 2010) while lindane and dieldrin is suggested to contribute to their neurotoxicity by altering the levels of estrogen receptor and its mediated signalling in neurons (Briz et al 2011).…”
Section: Introductionmentioning
confidence: 99%